Relationship of physical fitness profile and the number of technical error at the stages of ski training among high class skiers with different training load structures - Lebedev, M. M.; Popkova, A. B.; Myakinchenko, E. B. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the relationship between the profile of physical fitness and the number of technical errors made when passing training routes at the stages of ski training by high-class skiers who have a different structure of training loads at the stage of physical training.